Psychiatric disorders in children with 16p11.2 deletion and duplication - Niarchou, Maria; Chawner, Samuel J. R. A.; Doherty, Joanne L.; Maillard, Anne M.; Jacquemont, Sébastien; Chung, Wendy K.; Green-Snyder, LeeAnne; Bernier, Raphael A.; Goin-Kochel, Robin P.; Hanson, Ellen; Linden, David E. J.; Linden, Stefanie C.; et al. (Translational psychiatry, 2019)
Deletion and duplication of 16p11.2 (BP4–BP5) have been associated with an increased risk of intellectual disability and psychiatric disorder. This is the first study to compare the frequency of a broad spectrum of psychiatric disorders in children with 16p11.2 deletion and duplication. We aimed to evaluate (1) the nature and prevalence of psychopathology associated with copy number variation (CNV) in children with 16p11.2 by comparing deletion and duplication carriers with family controls; (2) whether deletion and duplication carriers differ in frequency of psychopathology. 217 deletion carriers, 77 deletion family controls, 114 duplication carriers, and 32 duplication family controls participated in the study. Measures included standardized research diagnostic instruments. Deletion carriers had a higher frequency of any psychiatric disorder (OR = 8.9, p < 0.001), attention deficit hyperactivity disorder (ADHD) (OR = 4.0, p = 0.01), and autism spectrum disorder (ASD) (OR = 39.9, p = 0.01) than controls. Duplication carriers had a higher frequency of any psychiatric diagnosis (OR = 5.3, p = 0.01) and ADHD (OR = 7.0, p = 0.02) than controls. The prevalence of ASD in child carriers of deletions and duplications was similar (22% versus 26%). Comparison of the two CNV groups indicated a higher frequency of ADHD in children with the duplication than deletion (OR = 2.7, p = 0.04) as well as a higher frequency of overall psychiatric disorders (OR = 2.8, p = 0.02) and psychotic symptoms (OR = 4.7, p = 0.02). However, no differences between deletion and duplications carriers in the prevalence of ASD were found. Both deletion and duplication are associated with an increased risk of psychiatric disorder, supporting the importance of early recognition, diagnosis, and intervention in these groups.